APPLICATION OF SUSTAINABLE RAINWATER MANAGEMENT PRACTICES TO PREVENT FLOOD RISKS IN J. ALUNANA PARK - Dunda, Andra; Matisovs, Ivars (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2020)
Using the principles of sustainable rainwater management systems, to find solutions for the prevention of floods and floods in the Veseta River in the territory of Madona district, Kalsnava parish, Jaunkalsnava village Juris Alunāns park. Latvia is rich in natural water resources, but climate change forecasts show that problems are possible. Aware that water is a natural resource that must be used conscientiously and responsibly, flood and flood waters should be seen as a resource. Such a resource needs to be used efficiently by sustainable rainwater systems. Water is an independent and irreplaceable need for plants, so the use of flood and flood water in the nursery irrigation system can be considered as a rational and efficient method. Historical research provides support for the potential of treated wastewater or accumulated rainwater. Such waters can be a source to provide plants with water while reducing the amount of fertilizer used.